Pemberdayaan Masyarakat Desa Pematang Serai melalui Pengabdian Mahasiswa Berbasis Moderasi Beragama dan Lingkungan - Marpaung, Hamdan Sudirman; Al Khoir, Akhyar; Putra, Irham Prasetyo; Utami, Dian Aulya; Nasution, Yusuf Ramadhan (Jurnal IPTEK Bagi Masyarakat, 2025)
Community Service Program (KKN) is a form of student community service implemented as part of the Tri Dharma of Higher Education. This article discusses the implementation of KKN in Pematang Serai Village, Tanjung Pura District, Langkat Regency, North Sumatra, with a focus on the role of students in carrying out community service. The background of this activity focuses on how KKN students are able to synergize with the community and support community development in terms of economics, religion, and education. This activity aims to be a means for students to learn so they are able to face problems that occur in the community. The method used is a qualitative descriptive research approach. By actively involving the community in the planning, implementation, and evaluation of the program, this study aims to understand in depth how the KKN program has impacted the lives of village communities. The results of this activity indicate that the role of KKN students has had significant benefits for the village community. In its implementation, this also helps students understand the needs and problems of the community directly. The Community Service Program in Pematang Serai Village, which includes the Indonesian Pious Children Festival, Tabligh Akbar, Planting Movement, Fish Seed Distribution, and Compost Making, is a real effort to realize religious moderation, improve environmental quality, and empower the community.